The Effectiveness of Predict Observe Explain Learning Model to Students’ Critical Thinking Skills - Cut Eka Para Samya; Muhibbuddin Muhibbuddin; Suhrawardi Ilyas (STKIP Singkawang, 2021)
This research aims to understand the differences of critical thinking skill in learning physics using predict observe explain (POE). It was experimental research with pretest posttest control group. It was conducted in class XI IPA of SMAN 3 Banda Aceh on the topic of thermodynamic law. This research used two parallel classes, which is the first class stands for control and another is used as experiment. Conventional model is applied in control class, whereas class of experiment had predict observe explain model. Instrument of this research was objective test with five multiple choice. Then, data were collected through pretest and posttest. Data analysis is carried out by comparing initial and final skills of students and then tested for significance using two different means through independent simple t-test. The results showed that there were differences in critical thinking skills between students using POE model and students using non-POE model. Therefore, it can be concluded that application of learning model predict observe explain in improving students critical thinking skills.